Hypersensitivity to chemotherapeutic drugs for the treatment of neoplasms. Literature review - S.V. Zaikov; M.A. Lykova; N.A. Hritsova; L.V. Veselovsky (Infusion & Chemotherapy)
BACKGROUND. Like any other drug, chemotherapy drugs can cause hypersensitivity reactions and are the third leading cause of drug-induced anaphylaxis deaths in the United States. Timely detection of hypersensitivity reactions to chemotherapeutic drugs in oncology is extremely important because, unlike other drugs (for example, antibiotics or anesthetics), which can be relatively easily replaced by others, chemotherapeutic drugs are often unique and indispensable for the treatment of neoplasms. In such situations, the doctor should evaluate the benefits of continuing treatment in comparison with the risk of a potentially fatal anaphylactic reaction when continuing chemotherapy with the drug that caused the development of hypersensitivity reactions, and also look for the possibility of replacing the chemotherapeutic drug that has become an allergen with another one.